1992
DOI: 10.1105/tpc.4.6.621
|View full text |Cite
|
Sign up to set email alerts
|

Cutinase is not required for fungal pathogenicity on pea.

Abstract: Cutinase, a fungal extracellular esterase, has been proposed to be crucial in the early events of plant infection by many pathogenic fungi. To test the long-standing hypothesis that cutinase of Nectria haematococca (Fusarium solani f sp piso is essential to pathogenicity, we constructed cutinase-deficient mutants by transformation-mediated gene disruption of the single cutinase gene of a highly virulent N. haematococca strain. Four independent mutants were obtained lacking a functional cutinase gene, as confir… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
63
0

Year Published

1994
1994
2002
2002

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 123 publications
(63 citation statements)
references
References 15 publications
0
63
0
Order By: Relevance
“…The wild-type 77-2-3 showed a single major hybridizing band with EcoRI, Hindlll, Pstl, and Sstl, and the location of the band was shifted as expected as a result of the gene disruption (data not shown). Figure 7 shows the results obtained with Kpnl, which demonstrates gene disruption as has been previously reported (Stahl and Schafer, 1992) and shows that the isolates used for inoculation were the same as those present at the end of the experiment. As seen previously , isolate T-8 showed multiple cutinase bands, including a band corresponding to that found in the wild-type isolate 77-2-3 (Figure 7).…”
mentioning
confidence: 66%
See 3 more Smart Citations
“…The wild-type 77-2-3 showed a single major hybridizing band with EcoRI, Hindlll, Pstl, and Sstl, and the location of the band was shifted as expected as a result of the gene disruption (data not shown). Figure 7 shows the results obtained with Kpnl, which demonstrates gene disruption as has been previously reported (Stahl and Schafer, 1992) and shows that the isolates used for inoculation were the same as those present at the end of the experiment. As seen previously , isolate T-8 showed multiple cutinase bands, including a band corresponding to that found in the wild-type isolate 77-2-3 (Figure 7).…”
mentioning
confidence: 66%
“…However, the amount of 3H-DipF labeling of extracellular proteins showed that 77-2-3 produced only 5 to 11% of extracellular active serine enzymes produced by T-8. With the cutinase gene-disrupted mutant, 3H-DipF-labeled cutinase could not be detected, although after 10 days small amounts of label were found in higher molecular weight components as previously found (Stahl and Schafer, 1992). Because the amount of extracellular fluid from the mutant used for SDS-PAGE was 10 times that from the wild type, these higher molecular weight proteins are only minor components.…”
mentioning
confidence: 76%
See 2 more Smart Citations
“…), Fusarium solani f. sp. pisi (Stahl and Schafer 1992), and Magnaporthe grisea (Sweigard et al 1992;Chap. 3, this Vol.…”
Section: A Dna Transformationmentioning
confidence: 99%